Anti-inflammatory effects and possible mechanism of action of lupeol acetate isolated from Himatanthus drasticus (Mart.) Plumel - Alves Victor CC; Lopes Amanda A; Leal Luzia; Silva Aline H; Veras Helenicy NH; Bandeira Mary; Lucetti Elaine CP; Lucetti Daniel L; Silva Gabriela S; Brito Gerly; Viana Glauce B (Journal of Inflammation, 2010)
Abstract Background The species Himatanthus drasticus is popularly known in Northeast Brazil as "janaguba" and belongs to the family Apocynaceae. The latex collected from its stem bark is used for several purposes including anti-inflammatory properties and presents among its bioactive constituents the pentacyclic triterpene lupeol. The objective of the present work was to study in vivo and in vitro the lupeol acetate (LA) isolated from the plant latex, in several models of inflammation. Methods Male Swiss mice (25-30 g, 6-24 animals per group) were administered with LA, 30 min before the test initiation. In the evaluation of analgesic activity the formalin test was used. The anti-inflammatory activity was evaluated by the following tests: paw edema induced by carrageenan and dextran, and the carrageenan-induced neutrophil migration into peritoneal cavities. Furthermore, the effect of LA on the myeloperoxidase release (MPO, an inflammation biomarker) from human neutrophils was also determined, as well as its antioxidant potential by the DPPH assay. Results In the formalin test, LA (10, 25 and 50 mg/kg, i.p.) inhibited both the 1st (neurogenic, 0-5 min) and mainly the 2nd (inflammatory, 20-25 min) phase. Naloxone completely reversed the LA effect, indicating the participation of the opioid system. LA also significantly inhibited carrageenan- and dextran-induced paw edemas, as well as the neutrophil migration to the peritoneal cavity evaluated by the carrageenan-induced pleurisia. In this model, the effect of a very low dose of LA (0.1 mg/kg) was potentiated by the same dose of pentoxifylline (PTX), a known TNF-alpha inhibitor. LA (25 and 50 μg/ml) was also very effective in inhibiting MPO released from stimulated human neutrophils, and significantly decreased the number of cells expressing iNOS activity in the paw of mice submitted to carrageenan-induced edema, suggesting a drug involvement with the NO system. Conclusions The anti-inflammatory effect of LA probably involves the opioid system, as indicated by the complete blockade of the opioid antagonist naloxone. Furthermore, the LA effect was potentiated by PTX (a TNF-alpha inhibitor). LA also decreased the number of iNOS cells, suggesting the participation of pro-inflammatory cytokines and the NO system in the drug action.